Bacterial viability on chemically modified silicon nanowire arrays. Issue 18 (15th March 2016) - Susarrey-Arce, A.; Sorzabal-Bellido, I.; Oknianska, A.; McBride, F.; Beckett, A. J.; Gardeniers, J. G. E.; Raval, R.; Tiggelaar, R. M.; Diaz Fernandez, Y. A.
Abstract : Multi-functional silicon nanowires (SiNWs) arrays: (I) nanostructure topography in the form of SiNWs, (II) covalent chemical modification with APTES and (III) incorporation of chlorhexidine digluconate. Abstract : The global threat of antimicrobial resistance is driving an urgent need for novel antimicrobial strategies. Functional surfaces are essential to prevent spreading of infection and reduce surface contamination. In this study we have fabricated and characterized multiscale-functional nanotopographies with three levels of functionalization: (1) nanostructure topography in the form of silicon nanowires, (2) covalent chemical modification with (3-aminopropyl)triethoxysilane, and (3) incorporation of chlorhexidine digluconate. Cell viability assays were carried out on two model microorganisms E. coli and S. aureus over these nanotopographic surfaces. Using SEM we have identified two growth modes producing distinctive multicellular structures, i.e. in plane growth for E. coli and out of plane growth for S. aureus . We have also shown that these chemically modified SiNWs arrays are effective in reducing the number of planktonic and surface-attached microorganisms.